Double pandemic: racial discrimination amid coronavirus disease 2019. Issue 1 (2020) - Addo, Isaac Yeboah
Abstract: The emergence of the COVID-19 pandemic has seen an escalation of racial discrimination against non-citizens and people of colour in many places around the world. While this COVID-19-related racial discrimination against non-citizens and people of colour has drawn much attention in the media space, the issue has been less discussed in academia. Given that racial discrimination has a significant impact on human relations, mental health, and general well-being, it is important to address the rising racial discrimination problem amid the COVID-19 pandemic. This paper discusses some of the reported stories of racial discrimination associated with COVID-19 and presents viewpoints on why people are being abused and the socio-economic implications associated with the abuse. The paper concludes with few suggestions on how to address the COVID-19 related racial discriminations as the world continues to fight against the double pandemic.